2019
DOI: 10.1002/aic.16503
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative study of the structure–activity relationship in hierarchical zeolites using liquid‐phase reactions

Abstract: Instructions for contributors Inside back coverCover illustration. Hierarchical zeolites made of intergrown nanosheets offer short diffusion lengths allowing for catalytic reactions to proceed in the zeolite micropores in the absence of diffusion limitations. At the same time, catalysis of desirable or undesirable reactions can take place in the mesopores. Using a model reaction and by systematic variation of nanosheet thickness with nanometer (single-unit-cell) precision, it is demonstrated that reaction-diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 42 publications
4
43
0
Order By: Relevance
“…Turn over frequency (TOF) of ethanol dehydration to diethyl ether in the absence of DTBP remains similar across all materials tested indicating that the nature of active sites as probed by this reaction remains unaltered (Table S3). The fraction of external sites of SPP (47 %) is much higher than that of tk‐SPP (21 %) and both conform with the expected (developed earlier based on geometric arguments) dependence on high‐aspect‐ratio nanosheet half‐thickness along b ( x p ) shown in Figure a. The external Brønsted acid site fractions of SPP and tk‐SPP increase upon steam treatment from 47 % to 51 % and from 21 % to 27 %, respectively.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Turn over frequency (TOF) of ethanol dehydration to diethyl ether in the absence of DTBP remains similar across all materials tested indicating that the nature of active sites as probed by this reaction remains unaltered (Table S3). The fraction of external sites of SPP (47 %) is much higher than that of tk‐SPP (21 %) and both conform with the expected (developed earlier based on geometric arguments) dependence on high‐aspect‐ratio nanosheet half‐thickness along b ( x p ) shown in Figure a. The external Brønsted acid site fractions of SPP and tk‐SPP increase upon steam treatment from 47 % to 51 % and from 21 % to 27 %, respectively.…”
Section: Resultssupporting
confidence: 85%
“…Understanding and controlling the water vapor‐induced structural rearrangements at the nanometer (single‐unit‐cell) level is of particular significance for two‐dimensional (2D) zeolites and thicker nanosheets that constitute an emerging class of catalysts, adsorbents and membranes . Herein, we demonstrate that an all‐silica single‐unit‐cell meso /microporous MFI‐type zeolite (SPP: self‐pillared pentasil) retains its crystallinity and micro‐ and mesoporosity under steaming at 350 °C, while small but detectable changes take place in the content of silanol groups and the enthalpy of transition (Δ H Transition ) relative to α‐quartz (the most stable polymorph of silica under ambient conditions). Electron microscopy reveals major changes in the nanosheet dimensions: increase in thickness along the b ‐direction (straight pore channels) and reduction of basal ((010) plane) dimensions along the c ‐direction.…”
Section: Introductionmentioning
confidence: 96%
“…It is observed that the uptake of benzyl alcohol per acid site is lower for the 2D MFI (25) catalyst than the 2D MFI (144) catalyst. The reaction studied in this work proceeds through the adsorption of benzyl alcohol on the catalyst surface . Assuming the strength of the acid sites does not change with varying the Si/Al ratio, the higher availability of the reactant molecule (benzyl alcohol) per active site in the micropores for the 2D MFI (144) catalyst is consistent with its higher effectiveness factor in the case of the reaction with the DTBP poisoning and its higher TOF, as compared to the 2D MFI (25) catalyst.…”
Section: Resultsmentioning
confidence: 72%
“…The reaction studied in this work proceeds through the adsorption of benzyl alcohol on the catalyst surface. [33] Assuming the strength of the acid sites does not change with varying the Si/Al ratio, [34] the higher availability of the reactant molecule (benzyl alcohol) per active site in the micropores for the 2D MFI (144) catalyst is consistent with its higher effectiveness factor in the case of the reaction with the DTBP poisoning and its higher TOF, as compared to the 2D MFI (25) catalyst. This is possibly due to steric crowding or repulsive interactions between the adsorbed reactant molecules, similar to what has been suggested for other reactions.…”
Section: Benzyl Alcohol Adsorption Isothermsmentioning
confidence: 87%
See 1 more Smart Citation